2017
DOI: 10.1002/brb3.656
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting dorsolateral prefrontal cortex by rTMS reduces the P300 based marker of deception

Abstract: ObjectiveQuite many studies have revealed certain brain‐process signatures indicative of subject's deceptive behavior. These signatures are neural correlates of deception. However, much less is known about whether these signatures can be modified by noninvasive brain stimulation techniques representing methods of causal intervention of brain processes and the corresponding behavior. Our purpose was to explore whether such methods have an effect on these signatures.MethodsIt is well known that electroencephalog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Their results showed that initial planning times could be influenced differently either by stimulating the right or the left hemisphere, with results directly dependent of hemisphere dominance—right hemisphere inhibition resulted in increased planning times and contralateral inhibition showed faster planning [ 22 ]. Such evidence is similarly defendable for ERPs global performance, since using a inhibitory stimulation over the frontal area originated decreases ERP amplitude in a modified P300 protocol [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that initial planning times could be influenced differently either by stimulating the right or the left hemisphere, with results directly dependent of hemisphere dominance—right hemisphere inhibition resulted in increased planning times and contralateral inhibition showed faster planning [ 22 ]. Such evidence is similarly defendable for ERPs global performance, since using a inhibitory stimulation over the frontal area originated decreases ERP amplitude in a modified P300 protocol [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, TMS pulsed at later SOAs beyond the range used here may have affected frontal processing also associated with deception, as indicated by later frontally distributed ERP components that have been shown to be involved with deception (e.g., Johnson et al, 2008 ). Future studies might want to more closely coordinate ERPs, as proxies for the dynamics of processing, with the timing of TMS pulses: for example, using a closed loop TMS approach by sending pulses when changes in ERP magnitude are detected, therefore replicating, and extending Karton and Bachmann ( 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two early studies applied TMS over the motor cortex and found greater cortico-spinal excitability while subjects responded with lies compared to truth (Lo et al, 2003 ; Kelly et al, 2009 ). Five studies focused on stimulation of prefrontal cortex (PFC), and while one of them did not show any differences between truth conditions caused by TMS (Verschuere et al, 2012 ), a series of four other experiments conducted by the same group demonstrated significant TMS effects on deception processes (Karton and Bachmann, 2011 , 2017 ; Karton et al, 2014a , b ). Indeed, using both online and offline TMS, Karton and associates found hemispheric differences between truth and lie conditions, with a lower number of deceptive responses with stimulation to left PFC compared to right, as well as an abolishment of the difference seen between truth conditions in the electrical P300 evoked response.…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex is a critical brain region for complex higher-order task-control functions [7, 46], including enacting plans, rules [47], and strategies [48]. Furthermore, disruption of the dorsolateral prefrontal cortex by rTMS reduces the P300-based marker of deception [49]. Additionally, Johnson-Frey et al [50] reported that the left parietal cortex is a critical region for the planning of skilled movements, indicating that the parietal regions are related to the execution of deception [50, 51].…”
Section: Discussionmentioning
confidence: 99%